EMPOWERMENT OF THE BENEFICIARY FAMILY (KPM) OF THE HOPE FAMILY PROGRAM (PKH) THROUGH THE SOCIAL ENTREPRENEURSHIP PROGRAM (PROKUS) IN CILEBAR DISTRICT, KARAWANG REGENCY - Umi Hani (Sean Institute, 2023)
Prokus is a program launched by the Ministry of Social Affairs of the Republic of Indonesia which targets beneficiary families (KPM) who have graduated or left the Family Hope Program (PKH) so that independence is formed. economically so that they do not go back down economically after they no longer receive assistance through PKH. Graduation KPM-PKH themselves are those who are still in the poor and vulnerable category but are graduated because some of the components do not fulfill them. As stated by the Director General of Social Empowerment of the Indonesian Ministry of Social Affairs,